Efl Teachers’ Concepts on Critical Reading Skills and Their Critical Reading Strategies At MAN 1 Polewali Mandar - Citra Resmi Megania; Abdul Haris Sunubi; Arqam; Ambo Dalle; Mujahidah (Universitas Muhammadiyah Palu, 2024)
Critical reading skills refer to the ability to analyze, evaluate, and interpret texts effectively. These skills go beyond basic comprehension and involve a deeper engagement with the conten. The research aimed to examine what things EFL Teachers use to develop their critical reading skills and to find out what impacts arise for EFL Teachers and students when they apply the knowledge and strategies of critical reading. This research used Qualitative research with study cases approach with source of data primer and secondary data with the informan of 3 English Teacher at MAN 1 Polewali Mandar, technique of analysiss used data reduction, display data dan conclution. The result of this research were as follow: 1) English EFL Teachers develop their critical reading skills that contribute to their teachingactively students showed critical reading skills proved by engaging in practices such as annotating, previewing, questioning, reflecting, outlining, summarizing, and evaluating which teachers enhance students ability using materials effectively contributing students critical reading skills. 2) The impact of the EFL Teachers's knowledge of critical reading skills and the use of these critical reading strategies in teaching showed good impact toward students ability specially for teachers possess a solid grasp of critical reading techniquessuch as identifying main ideas, analyzing arguments, evaluating evidence, and synthesizing information which teacher can create enriching learning experiences for students through structured activities and guided discussionsdeeper engagement with test and learning activates during classroom.